Applying the Porosity-to-Cement Index for Estimating the Mechanical Strength, Durability, and Microstructure of Artificially Cemented Soil - Jair Arrieta-Baldovino; Ronaldo Izzo; Carlos Millan-Paramo (Civil Engineering Journal, 2023)
Fine, expansive, and problematic soils cannot be used in fills or paving layers. Through additions to these soils, they can be converted into technically usable materials in civil construction. One methodology to make them viable for construction is through a stabilization process. Nevertheless, current methodologies regarding dosage based on compaction effort and the volumetric amount of binder used are unclear. Thus, this research describes cement-stabilized sedimentary silt's strength and durability properties from Curitiba (Brazil) for future application in paving. Splitting tensile strength, unconfined compressive strength, and loss of mass against wetting and drying cycles (W-D) were investigated in the laboratory utilizing greenish-gray silt (originating from one of the Guabirotuba Formation layers, Paraná) and high-early strength Portland cement- ARI (CPV). Utilized were cement concentrations (C) of 3, 5, 7, and 9%, molding dry unit weights (d) of 14, 15, and 16 kN/m3, curing periods (t) of 7, 14, and 28 days, and constant moisture content (w) of 23%. With an increase in cement concentration and curing time, the compacted mixes demonstrate an increase in strength, an improvement in microstructure, and a decrease in accumulated mass loss (ALM) and initial porosity (η). Using the porosity/volumetric cement content ratio (η/Civ), the lowest amount of cement required to stabilize the soil in terms of strength and durability was determined. The porosity/cement index provided an appropriate parameter for modeling the mechanical and durability properties, and a unique equation between the strength/accumulated loss of mass and the porosity/binder index was obtained for the curing times studied. Lastly, C = 5% by weight is the minimum acceptable amount for prospective subbase soil application. Doi: 10.28991/CEJ-2023-09-05-02 Full Text: PDF